A new species of Plumarella (Octocorallia: Calcaxonia: Primnoidae) from the Northeast Pacific, and the redescription of Plumarella longispina Kinoshita, 1908 - Cairns, Stephen D.; Rodriguez-Bermudez, Adriana (Zootaxa, 2024)
A new species of primnoid octocoral, Plumarella williamsi, is described from the west coast of the Unites States, ranging from Baja California to Washington at 55–735 m. Previously reported as the Japanese species P. longispina Kinoshita, 1908, it differs from that species in having fewer and more massive body wall scales, taller marginal scales, and larger and less granular coenenchymal scales. In addition, a phylogenetic tree analysis further confirms the status of the new species, and places P. williamsi as closely related to P. aurea (Deichmann, 1936) and P. longispina Kinoshita, 1908. Plumarella longispina is also redescribed based on type and topotypic specimens.